Mechanism of novel defect multiplication impacting high power 4H-SiC devices - N.A. Mahadik; M. Dudley; B. Raghothamachar; Z. Chen; R.E. Stahlbush; M. Hinojosa; A. Lelis; W. Sung (Materials & Design, 2024)
Basal plane dislocations and stacking faults are critical defects influencing silicon carbide (SiC) based high power devices that are rapidly emerging to enable the future needs of electric vehicles, locomotives, renewables, and grid-scale applications. Microstructural properties of three novel interactions between basal plane dislocations and threading mixed dislocations (TMDs) are described. This leads to multiplication of Shockley stacking faults (SSFs) in SiC epitaxial layers. First is a mechanism of double interaction of two SSFs with TMDs that causes the SSFs to glide on multiple basal planes, and creation of locked partial dislocation dipoles (PDD) due to the attractive force between the opposite sign partial dislocations. Second type of interaction occurs between SSFs and a tilted TMD, that results in formation of another SSF. The third type of interaction causes further SSF multiplication by unlocking previously created PDDs. This occurs when the newly formed SSF intersects with the previously locked PDD, and unlocks it, leaving behind a freely gliding partial dislocation and formation of another SSF. Multiplication of SSFs can severely degrade reliability and performance of high power SiC devices by increasing reverse leakage current and on-state resistance, and could eventually lead to device failure.